Surgical experience is predictive for bladder tumour resection quality. (2nd November 2022) - Bube, Sarah H.; Brix, Rasmus; Christensen, Maya B.; Thostrup, Mathias; Grimstrup, Søren; Hansen, Rikke B.; Dahl, Claus; Konge, Lars; Azawi, Nessn
Abstract: Objectives: To assess the resection quality of transurethral bladder tumour resection (TURBT) and the association to surgeon experience depending on the presence of detrusor muscle. Methods: A retrospective study on 640 TURBT procedures performed at Zealand University Hospital, Denmark, from 1 January 2015 − 31 December 2016. Data included patient characteristics, procedure type, surgeon category, supervisor presence, surgical report data, pathological data, complications data and recurrence data. Analysis was performed using simple and multiple logistic regression on the association between surgeon experience and the presence of detrusor muscle in resected tissue from TURBT. Results: Supervised junior residents had significant lower detrusor muscle presence (73%) compared with consultants (83%) (OR = 0.4, 95% CI = 0.21–0.83). Limitations were the retrospective design and the diversity of included TURBT. Conclusions: It was found that surgical experience predicts detrusor muscle presence and supervised junior residents performing TURBT on patients resulted in less detrusor muscle than consultants.